2021
DOI: 10.3389/fvets.2021.701377
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of the Fluid Challenge Approach in Goal-Directed Fluid Therapy: What Can We Learn From Human Studies?

Abstract: Resuscitative fluid therapy aims to increase stroke volume (SV) and cardiac output (CO) and restore/improve tissue oxygen delivery in patients with circulatory failure. In individualized goal-directed fluid therapy (GDFT), fluids are titrated based on the assessment of responsiveness status (i.e., the ability of an individual to increase SV and CO in response to volume expansion). Fluid administration may increase venous return, SV and CO, but these effects may not be predictable in the clinical setting. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 144 publications
(355 reference statements)
0
5
0
Order By: Relevance
“…As a patient approaches the plateau portion of the curve, atrial pressure increases which leads to increased venous and pulmonary hydrostatic pressures (56). The combined increase in pressures, along with increased natriuretic peptides, result in a shift of fluid from the intravascular to the interstitial space and ultimately leads to pulmonary and peripheral edema (57). Tissue edema impairs oxygen and metabolite diffusion, and distorts capillary blood flow with a profound effect on the venous pressure and function in vital organs (58).…”
Section: Predictors Of Fluid Responsivenessmentioning
confidence: 99%
“…As a patient approaches the plateau portion of the curve, atrial pressure increases which leads to increased venous and pulmonary hydrostatic pressures (56). The combined increase in pressures, along with increased natriuretic peptides, result in a shift of fluid from the intravascular to the interstitial space and ultimately leads to pulmonary and peripheral edema (57). Tissue edema impairs oxygen and metabolite diffusion, and distorts capillary blood flow with a profound effect on the venous pressure and function in vital organs (58).…”
Section: Predictors Of Fluid Responsivenessmentioning
confidence: 99%
“…Our study has several strength points (1) we conducted all steps in strict accordance with the Cochrane Handbook of Systematic Reviews for interventions, (2) we followed the standard reporting guidelines of PRISMA statement to report this work, (3) we ran a comprehensive search of multiple electronic databases to identify all relevant studies, and finally (4) Our study reported class 1 evidence about the efficacy of GDFT during pregnancy. Nonetheless, our study has a few limitations.…”
Section: Strength Points and Limitationsmentioning
confidence: 99%
“…Rapid volume expansion by administration of intravenous fluid is essential for patients undergoing major surgeries or patients with poor volume expansion as they need to maintain tissue perfusion [1] . One of the most efficient methods of intravenous therapy is goal-directed fluid therapy (GDFT) [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Total intravenous crystalloid infusion in the 24-hour postoperative period was derived from the medical record J Thorac Dis 2022;14 (7):2602-2610 | https://dx.doi.org/10.21037/jtd-22-707 and defined as the volume of crystalloid administered in the 24-hour postoperative period. Initially, patients were classified into four groups representing incremental quartiles of the exposure variable of the total intravenous crystalloid infusion in the 24-hour postoperative period (8,12).…”
Section: Exposure Variablementioning
confidence: 99%
“…Healthy people have a certain preload reserve capacity, and they have the ability to self-regulate on the ascending limb of the Frank-Starling curve without the need for additional fluid supplementation ( 7 ). Insufficient intravascular volume to patients who are fluid responsive can be adapted by self-adjustment, and excessive perioperative fluid administration to these patients may increase the risks of fluid overload without conferring additional benefit ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%